Assessing the Efficiency of an Active Viscous Damper in Near-Field and Far-Field Earthquakes - Ali Jalaeefar (Iranian Society of Structrual Engineering (ISSE), 2021)
The present article involves evaluating the efficiency of an active viscous damper in controlling vibrations caused by near and far field earthquakes. Being installed on chevron bracing systems, the damper is able to provide necessary controlling forces to diminish vibration amplitude up to its' saturation limit. Many researchers have worked on the concept of seismic active control under far field waves. But the efficiency of this system is not guaranteed in near field ones due to time delay phenomenon. Pulse and shock entity of near field seismic waves leads to decreasing active control effects and the present research also proves the fact. A computer based algorithm is developed using Newmark instantaneous optimal control method in MATLAB software.The performance of this code is validated and evaluated based on three different reference problems. Then the analysis results of a 7-storey structure are calculated based on the code. The analyses are developed using both controlled and uncontrolled states. Also near field and far field earthquake records are used in this process and the results are compared in different tables and graphs. Based on the results, it seems that active control systems in spite of their effectiveness in near field earthquakes, needs necessary scheming and changes in the process.